Pengaruh Pertumbuhan Ekonomi dan Harga Saham Terhadap Pertumbuhan Laba pada Perusahaan Pertambangan Sub Sektor Logam dan Mineral yang Terdaftar di Bursa Efek Indonesia - Dike Surenjani; Wahyu Indah Mursalini; Afni Yeni (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to 1. To find out how much influence economic growth has on profit growth, 2. To find out how much influence stock prices have on earnings growth, 3. To find out how much influence economic growth and stock prices have on earnings growth. The background of this research is that if the rate of return on profits is not as expected, the company will experience bankruptcy. So that this does not happen the company must be able to overcome these problems by paying attention to the state of the economy and stock prices in order to stay alive. The sample in this study were 8 mining companies in the metal and mineral sub-sector listed on the Indonesia Stock Exchange.Based on the results of statistical analysis, it can be concluded that economic growth has a significant effect on profit growth. This is evidenced by the results of the partial test with a significant value of 0,036 < 0,05. While the stock price has no significant effect on profit growth. This is evidenced by the results of the partial test with a significant value of 0,886 > 0,05. Then together there is also no significant effect between economic growth and stock prices on profit growth. This is evidenced by the results of the simultaneous test with a value of 0,103 > 0,05.